2007
DOI: 10.1051/limn/2007023
|View full text |Cite
|
Sign up to set email alerts
|

Indicator taxa of benthic diatom communities: a case study in Mediterranean streams

Abstract: A key issue in the implementation of the Water Framework Directive is the classification of streams and rivers using biological quality parameters and type-specific reference conditions. Four groups of stream types were defined in NE Spain on the basis of 152 diatom samples by means of detrended correspondence analysis and classification techniques. Diatom analysis was restricted to epilithic taxa, and the sites included gradients ranging from near-natural streams to sites with poor ecological quality. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 31 publications
1
35
1
10
Order By: Relevance
“…Tornés et al, 2007). Indeed, pollution is often considered as homogenising species composition (Leira and Sabater, 2005;Pan et al, 1999;Tornés et al, 2007). But pollution was not the overriding parameter in our study area since high altitude lakes are upstream most of human activities.…”
Section: Local Factors Impact More Diatom Communities Composition Thamentioning
confidence: 80%
See 3 more Smart Citations
“…Tornés et al, 2007). Indeed, pollution is often considered as homogenising species composition (Leira and Sabater, 2005;Pan et al, 1999;Tornés et al, 2007). But pollution was not the overriding parameter in our study area since high altitude lakes are upstream most of human activities.…”
Section: Local Factors Impact More Diatom Communities Composition Thamentioning
confidence: 80%
“…Groups A2 and B2 were represented by only one lake therefore indicator species were not possible to calculate for these groups. (Tornés et al, 2007). Moreover, E. subminuta, which is an indicative species of this community, is usually leaving in calcareous ecosystems (Hofmann et al, 2011).…”
Section: Diatom Communities Of Higher Conductivities Lakes (A3)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, many studies have shown a strong relationship between streamflow reductions and benthic response in Mediterranean-climate streams (Bonada et al, 2006(Bonada et al, , 2007aTorne´s et al, 2007;Morais, 2008). Furthermore, prolonged drought in Mediterranean-climate regions has particularly strong effects on the abundance and composition of benthic-macroinvertebrate communities in small streams (Beˆche et al, 2006;Beˆche and Resh, 2007a, b).…”
Section: Introductionmentioning
confidence: 99%